2016
DOI: 10.1120/jacmp.v17i3.5959
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of patient setup uncertainty of stereotactic radiotherapy with the frameless 6D ExacTrac system using statistical modeling

Abstract: The purpose of this study is to evaluate patient setup accuracy and quantify individual and cumulative positioning uncertainties associated with different hardware and software components of the stereotactic radiotherapy (SRS/SRT) with the frameless 6D ExacTrac system. A statistical model is used to evaluate positioning uncertainties of the different components of SRS/SRT treatment with the Brainlab 6D ExacTrac system using the positioning shifts of 35 patients having cranial lesions. All these patients are im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…Here, significant effort is required in order to ensure effective mask immobilization and, in certain cases, even with the mask, large systematic drifts of up to several millimeters from initial setup have been reported (Amelio et al, 2013; Fuss et al, 2004; Murphy, 2009). In a recent study uncertainties as large as 5.84 mm and 2.4 degrees were reported and were found to correspond to cases where patients do not setup appropriately because of the limited manufacturing quality of the mask, loosening or shrinkage of the mask during treatment, or physical changes of the patient's head during treatment due to swelling of the face (Keeling et al, 2016). As a result, treatment interruption for intrafractional patient realignment can occur to ensure proper target coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Here, significant effort is required in order to ensure effective mask immobilization and, in certain cases, even with the mask, large systematic drifts of up to several millimeters from initial setup have been reported (Amelio et al, 2013; Fuss et al, 2004; Murphy, 2009). In a recent study uncertainties as large as 5.84 mm and 2.4 degrees were reported and were found to correspond to cases where patients do not setup appropriately because of the limited manufacturing quality of the mask, loosening or shrinkage of the mask during treatment, or physical changes of the patient's head during treatment due to swelling of the face (Keeling et al, 2016). As a result, treatment interruption for intrafractional patient realignment can occur to ensure proper target coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Figures and show the accuracy of the patient setup at a couch angle of 0º for SRS/SRT treatment at our institution. Keeling et al reported that the mean translational XC shifts for each of 49 patient treatments were almost from − 2.5 to + 2.5 mm, and those SD values were much less than 1.0 mm in SRS/SRT with the frameless 6D ExacTrac system . It was suggested that our results were larger than theirs because a localizer box was not used in the CT simulation, and all patients were set up at the isocenter position manually in the SRS/SRT treatments at our institution.…”
Section: Discussionmentioning
confidence: 65%
“…A noninvasive thermoplastic mask (BrainLAB A.G., Heimstetten, Germany) was used to immobilize all patients in SRS/SRT for intracranial lesions. A previous report mentioned descriptions of this thermoplastic mask system . In this study, we did not use a localizer box in the CT simulation, but we marked the CT origin coordinate on the noninvasive thermoplastic mask directly as same as the conventional radiation therapy procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations